LAW ENFORCEMENT IN CASES OF MURDER CONTINUED BY SEXUAL VIOLENCE AGAINST CHILDREN - Wijaya, Sudarma; DM, M. Yusuf; Dewi, Sandra (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
In many cases, perpetrators attempt to cover their tracks by killing the victim, making biological evidence difficult to find. This requires the police to work extra hard to collect forensic evidence and witness statements. The purpose of this study is to analyze law enforcement in cases of murder followed by sexual violence against children based on Law Number 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection at the Indragiri Hulu Police. The method used is sociological legal research. Based on the results of the study, it is known that law enforcement in cases of murder followed by sexual violence against children based on Law Number 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection at the Indragiri Hulu Police that the authorities have implemented the provisions of Law Number 17 of 2016 strictly. This regulatory change provides a strong legal basis for investigators in applying the maximum criminal threat, including the death penalty, life imprisonment, or other aggravating crimes. The investigation process is directed to fulfill the principles of child protection, victim justice, and legal certainty. Obstacles such as the limited number of investigators with specialized competencies in handling child-based crimes, the lack of comprehensive forensic facilities, and the often-impeded availability of post-mortem examinations and laboratory results contribute to slow investigations. Furthermore, this contributes to the deep trauma experienced by victims and their families. Efforts to overcome these obstacles include increasing the capacity of officers through specialized training in handling sexual violence against children. Local governments and law enforcement institutions also need to strengthen supporting facilities. Coordination with integrated service agencies must be improved to expedite the process of establishing evidence and providing assistance to victims.